Integrated Structures of Corporations: Ukrainian Legal Reality - Kostruba, Anatoliy (Teisė, 2022)
The article is devoted to the study of legal nature of the mechanism for association of legal entities. Such associations of legal entities are realized in order to attract not only capital and other production resources, including labor, but also in order to satisfy nonproperty interests. Legal capacity of legal entities in the process of their merger is analyzed, based on what – statutory or contractual – association of corporations is determined. The statutory association does not lead to the creation of another fiction other than a legal entity, due to which it is ensured through its inherent organizational legal forms. The contractual association does not require the formation of a new legal entity (concern, consortium, association (union), syndicate, conglomerate, cartel, pool). In the event of such consolidation of legal entities, the contractual structure of a simple company or other joint activity is formed, formally close to such person at law as a legal entity. The difference between the above procedure of merging from the first option lies in the degree of autonomy of the members from each other, as well as in the expected result of such merger.